Centennial of the teaching of Gynecology in Peru - Bazul, Víctor (2015)
There are dates that can not be forgotten from the obstetricians, one is August 17. 100 years ago, Professor T. Constantino Carvallo, modest and illustrious San Marcos began teaching professor of gynecology for medical students of the Faculty of Medicine of San Fernando. The start of this apostolate was in a small room called Las Mercedes, built with his own money at the former Royal Hospital of Santa Ana, located where now the Maternal Perinatal Institute (Lima Maternity Hospital).